Effect of Nudge-Based Intervention on Adherence to Physician Visit Recommendations and Early Health Outcomes among Individuals Identified with Chronic Kidney Disease in Screens. Issue 1 (January 2022) - Fukuma, Shingo; Sasaki, Shusaku; Taguri, Masataka; Goto, Rei; Misumi, Toshihiro; Saigusa, Yusuke; Tsugawa, Yusuke
Significance Statement: Many individuals with CKD are not receiving appropriate medical treatments. Behavioral economics interventions, such as nudging strategies, are reported to improve health-related behaviors. However, little is known about whether the nudge intervention increases the likelihood of individuals with identified CKD adhering to a recommended physician visit. In this randomized clinical trial, 4011 participants in CKD screens were randomly assigned to two interventions or the control: ( 1 ) the nudge-based letter, ( 2 ) the clinical information letter, and ( 3 ) the control. The probability of visiting the recommended physician was higher among participants who received the nudge-based letter or the clinical letter compared with the control group. We found no evidence for interventions associated with improved early health outcomes. Abstract : Background: Although CKD screening programs have been provided in many settings, little is known as to how we can effectively translate those screening programs into improved health. Methods: We conducted a randomized clinical trial on national health screening for CKD in Japan between April 2018 and March 2019. A total of 4011 participants in CKD screening programs aged 40–63 years were randomly assigned to two interventions or the control, with a ratio of 2:2:1, respectively: ( 1 ) the nudge-based letter that contained a message on the basis of behavioral economics, ( 2 ) the clinical letter including general information about CKD risks, and ( 3 ) the control (informed only of the screening results). The main outcome was adherence to a recommended physician visit within 6 months of the intervention. The secondary outcomes were eGFR, proteinuria, and BP 1 year after the intervention. Results: Compared with the control group, the probability of undergoing a recommended physician visit was higher among participants who received the nudge-based letter (19.7% for the intervention group versus 15.8% for the control; difference, +3.9 percentage points [pp]; 95% CI, +0.8 to +7.0; P =0.02) and the clinical letter (19.7% versus 15.8%; difference, +3.9 pp; 95% CI, +0.8 to +7.0; P =0.02). We found no evidence that interventions were associated with improved early health outcomes. Conclusions: The behavioral economics intervention tested in this large RCT had limited effect on changing behavior or improving health outcomes. Although the approach has promise, this study demonstrates the challenge of developing behavioral interventions that improve the effectiveness of CKD screening programs. Clinical Trial registry name and registration number: University Hospital Medical Information Network Clinical Trial Registry, UMIN000035230